Acute Contained Ruptured Aortic Aneurysm Presenting as Left Vocal Fold Immobility - Sharon H. Gnagi; Brittany E. Howard; Joseph M. Hoxworth; David G. Lott (Case Reports in Otolaryngology)
Objective. To recognize intrathoracic abnormalities, including expansion or rupture of aortic aneurysms, as a source of acute onset vocal fold immobility. Methods. A case report and review of the literature. Results. An 85-year-old female with prior history of an aortic aneurysm presented to a tertiary care facility with sudden onset hoarseness. On laryngoscopy, the left vocal fold was immobile in the paramedian position. A CT scan obtained that day revealed a new, large hematoma surrounding the upper descending aortic stent graft consistent with an acute contained ruptured aortic aneurysm. She was referred to the emergency department for evaluation and treatment by vascular surgery. She was counseled regarding surgical options and ultimately decided not to pursue further treatment. Her vocal fold immobility was subsequently treated via office-based injection medialization two weeks after presentation and again 5 months after the initial injection which dramatically improved her voice. Follow-up CT scan at 8 months demonstrated a reduction of the hematoma. The left vocal cord remains immobile to date. Conclusion. Ortner’s syndrome, or cardiovocal syndrome, is hoarseness secondary to left recurrent laryngeal nerve palsy caused by cardiovascular pathology. It is a rare condition and, while typically presenting gradually, may also present with acute symptomatology.